Adapting to Climate Change in the Coastal Zone in Western Australia: Meanings, Dimensions, Effectiveness and Shortfalls of Collaborative Coastal Adaptation Planning - Danese Galano, Chiara (Curtin University, 2017)
The present study explores the features of and key challenges to collaborative coastal adaptation planning in Western Australia through a multiple case study approach. A set of governance principles is collated from the literature and then tested through in-depth interviews, workshops and participant observations in the case studies. The results are then used to further refine a set of principles of good governance specifically aimed at guiding a collaborative approach to coastal adaptation planning.